TEORI AL-HUDUD DAN PERMASALAHAN BUNGA BANK : TELAAH PEMIKIRAN MUHAMMAD SHAHRUR - Muhammad Muhaimin (LP2M IAIN Jember (now UIN Kiai Haji Achmad Siddiq Jember), 2020)
One of the characteristics of Islamic law is that it can be applied in all places and times, although the Qur'an and Hadith as its source are limited. This requires a method that can apply these characteristics in the modern world, in every circumstance and place. The thought that the law described in the Qur'an and the hadith contains restrictions (al-hudud), both upper and lower limits, is one method of applying the law so that the characteristics of Islamic law can be realized. The al-hudud's theory which has been formulated by Muhammad Shahrur can be used to solve various contemporary problems in the field of Islamic law and is an attempt to prove that Islamic law can answer the demands of the times. Shahrur offered to apply the law of usury to modern banking using this al-hudud theory so that the poor are not oppressed and the rich are not wrong.